The Last Word - Jan Boessenkool (Communicare)
As an organisational anthropologist I was very enthusiastic about the philosophy of the ubuntu concept when I heard and read about it a couple of years ago. It gave words and meaning to many of my experiences during long stays in different parts of Sub-Saharan Africa. The concept has a strong metaphoric power for African-based organisational and management theories, as opposed to Eurocentric and Americacentric ones: ‘We Africans will develop our own theories, based on our typical African authenticity and you, westerners can learn from us’. Instead of thinking in dichotomies, as we so typically do, it is possible and more fruitful to stress togetherness and the Rainbow Nation: instead of ‘or – or’ ‘and – and’; taking the African Renaissance as a starting point.